Aplikasi HijaiyahKu Berbasis Android - Muhamad Bahrul Ulum; Anik Hanifatul Azizah; Sandfreni Sandfreni (Jurnal Komputasi, 2022)
Early introduction to hijaiyah letter to children is important, for it is the basic of Al-Qur’an reading as Moslem’s guidance in life. Al-Qur’an reading learning method is often given in direct teaching by teachers with the help of books introducing and teaching hijaiyah letters. Introducing hijaiyah letters to children requires effective and engaging teaching method, one of them is by teaching by playing. Using games as medium will create fun atmosphere for an interactive teaching process. This Android based introducing method utilized prototype method, from research stage to application test stage. The result of this application design is an application that may help ease children in learning hijaiyah letters. With this application, children can learn about hijaiyah letters while playing, and train their memories and concentrations with the help of smartphone technology.